Testosterone An Unauthorized Biography - Jordan-Young, Rebecca M. (Harvard University Press, 2019)
Testosterone is neither the biological essence of manliness nor even the "male sex hormone." It doesn't predict competitiveness or aggressiveness, strength or sex drive. Rebecca Jordan-Young and Katrina Karkazis pry testosterone loose from more than a century of misconceptions that undermine science while making social fables seem scientific
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Aug 2021)
Keywords: SCIENCE / Life Sciences / Biology; Masculinity in popular culture; Testosterone -- Public opinion; Testosterone